KULEX-Hand: An Underactuated Wearable Hand for Grasping Power Assistance - Hong, Man Bok; Kim, Sin Jung; Ihn, Yong Seok; Jeong, Gu-Cheol; Kim, Keehoon (IEEE transactions on robotics, 2019)
In this paper, we present KULEX-hand, a novel underactuated hand exoskeleton for grasping power assistance for patients having a partially paralyzed hand or the elderly with weakened muscle strength. This mechanism consists of an underactuated finger for grasp motion generation, a spherical four-bar linkage for power transmission, and a passive thumb link with a flexure hinge structure. Based on the natural closing motion of the human index finger, the motion generation linkage was synthesized as a planar five-bar in which two input links were coupled with a four-bar linkage. Therefore, after contact occurs on the proximal link, the synthesized linkage can mimic the grasping motion of the human middle and distal phalanges. The kinetoelastic relation of the underactuated finger was derived using the theory of screws. Based on this relation, guidelines were proposed for selecting the springs for achieving a stable pinch grasp. A prototype was designed, and the naturalness of motion was evaluated from an experiment with five subjects.